Current and candidate additives for environmentally acceptable lubricants—A review - Wenbo Wang; Jun Qu (Friction)
The world consumes approximately 40 million tons of lubricants annually, and nearly half of them end up in the environment because of leaks, discharges, and evaporation, causing significant environmental and economic impacts. The need for moving toward environmentally acceptable lubricants (EALs) is increasingly being recognized. Synthetic ester, polyalkylene glycol, vegetable oil, and water are among the base fluids approved by the U.S. Environmental Protection Agency for EALs. However, neat base fluids cannot fully meet the lubrication requirements without incorporating functional additives such as anti-wear, antioxidant, corrosion inhibitor, and viscosity modifiers. Both the performance and environmental compatibility of lubricant additives are critical. In this article, current and candidate EAL additives, both in liquid and solid forms, are reviewed, with a focus on their functionalities in friction and wear reduction, toxicity, and biodegradability. Finally, a perspective for future research on EAL additives is discussed.